Thermocapillary actuation of liquid plugs using a heater array - Jiao, Zhenjun (2014)
With the aim toward realizing polymerase chain reaction (PCR) of deoxyribonucleic acid (DNA) in plug-based capillary platforms, this paper reports the theoretical and experimental results of thermocapillary actuation for temperature cycling with an arbitrary ramping function. Two concepts were investigated: (a) actuation and spatial temperature cycling with three heaters and (b) actuation and temporal cycling with two heaters. The paper first describes the analytical models of both concepts. The model considers the spatio-temporal heat transfer effects, which is coupled with the surface tension driven movement of the plug. In the experiments, both temperature field and plug motion were measured and evaluated. The temperature field was captured by an infrared thermal tracer camera. The position of the plugs was automatically captured and evaluated with a CCD camera. Finally, analytical and experimental results are compared and discussed.